Analysis of the Physical and Chemical Properties of Soil in the Riau University Arboretum - Pebriandi, Pebriandi; Marsanda, Gilang Panca; Desvita, Zeki; Sari, Efilda; Darlis, Vinny Volcherina; Oktorini, Yossi; Irfani, Ewi; Nugraha, Lefdi Agung; Pertiwi, Hutami Indah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Soil is an important component of forest ecosystems because it acts as a provider of nutrients, a support for vegetation, and a regulator of biogeochemical cycles. Variations in the physical and chemical properties of soil are greatly influenced by vegetation cover and soil depth. This study aims to analyse the chemical properties of soil in two types of vegetation cover, namely dense and moderate cover, in the Riau University Arboretum, which was determined using the Normalised Difference Vegetation Index (NDVI) method. Soil samples were taken at three depths (0–10 cm, 10–20 cm, and 20–30 cm) to determine the vertical variation in soil chemical properties. The parameters analysed included pH, organic carbon (organic C), total nitrogen (total N), phosphorus (P₂O₅), and potassium (K₂O). The results showed that soil pH was in the acidic category, ranging from 4.43 to 5.21. Organic carbon content was higher in the surface layer than in the lower layers, with the highest value of 5.14% in medium cover. Total N content was low in all samples (0.11–0.25%), indicating a limitation of nitrogen as a factor restricting vegetation growth. The nutrient elements P₂O₅ and K₂O tended to be higher in the surface layer, especially in dense cover (P₂O₅ = 26.66 mg/100 g; K₂O = 24.56 mg/100 g). In general, dense cover was able to maintain nutrient availability better than medium cover, although medium cover had relatively higher organic C content on the surface. These findings confirm that vegetation cover plays an important role in maintaining soil quality, and the preservation of dense vegetation needs to be optimised to support soil fertility and the sustainable conservation function of the arboretum.